Factors Related to Self-Reported Attention Deficit Among Incoming University Students. (September 2016) - Cheng, Shu Hui; Lee, Chih-Ting; Chi, Mei Hung; Sun, Zih-Jie; Chen, Po See; Chang, Yin-Fan; Yeh, Chin-Bin; Yang, Yen Kuang; Yang, Yi-Ching
Objective: This study was designed to explore physical, social/behavioral, and mental health factors among incoming university students with elevated self-reported ADHD symptoms.Method: A total of 5, 240 incoming university students were recruited. The test battery included the ADHD Self-Report Scale, the Measurement of Support Functions, the Chinese Internet Addiction Scale–Revision, Quality of Life assessment, the Brief Symptoms Rating Scale, and the 10-item Social Desirability Scale.Results: ADHD symptoms were elevated in 8.6% of the sample. Only individuals with a lower social desirability score, however, were recruited for further analysis. Significant influential factors for higher self-reported levels for ADHD symptoms included greater suicidal ideation and emotional disturbance, as well as a higher Internet addiction tendency, lower levels of social support, and a greater amount of exercise.Conclusion: Given the elevated prevalence of self-reported ADHD symptoms among this sample of university students, screening for these kinds of problems to detect early challenges before students fail in college as well as identify youth with undiagnosed ADHD should be considered.